The Complex Relationship Among Formal Thought Disorders, Neurocognition, and Functioning in Nonacutely Ill Schizophrenia Patients. Issue 1 (January 2020) - Comparelli, Anna; Corigliano, Valentina; Forcina, Francesca; Bargagna, Paride; Montalbani, Benedetta; Falcone, Giulia; Nardella, Adele; Stampatore, Lorenzo; Salzer, Mark; Pompili, Maurizio
Abstract : Abstract: The aims of the present study were to 1) evaluate clinical differences between patients suffering from schizophrenia (SZ) with mild versus moderate/severe formal thought disorder (FTD); 2) explore relationships between dimensions of FTD, neuropsychological domains, and global functioning; and 3) compare clinical dimensions of FTD in early and late SZ. One hundred thirty-six individuals with schizophrenia were recruited and evaluated during a nonacute phase of illness. FTD was assessed with the Thought, Language, and Communication Scale. Partial correlations, t -tests, and stepwise regression were undertaken to address the study aims. Patients with moderate/severe FTD performed worse than those with mild FTD for processing speed, reasoning and problem solving, and social cognition, and demonstrated poorer global functioning. Early SZ did not differ from late SZ in terms of negative FTD and difficulty in abstract thinking (DAT). Negative FTD was correlated with reasoning and problem solving; DAT was correlated with social cognition. All clinical dimensions of FTD, regardless of neurocognitive impairment, accounted for a significant amount of variance in global functioning. FTD predicted global functioning, regardless of neurocognitive factors. Due to their stability in different phases of the course of the disease and their strong relationship with other core variables, Neg-FTD and DAT should be investigated as an intermediate phenotype of the illness.